HUMAN TRAFFICKING: CAUSES AND IMPLICATIONS (International Journal of Food and Nutritional Sciences, 2022)
After the drug trade and the arms trade, human trafficking is the third biggest organized crime around the world. "Trafficking" is defined by the United Nations as "any activity that leads to the recruitment, transportation, sheltering, or receiving of people through the use of force, the threat of force, or a position of vulnerability." Around the world, 20% of human trafficking is carried out for forced labor and nearly 80% is done for sexual exploitation